Journal of Economic Structures The Official Journal of the Pan-Pacific Association of Input-Output Studies (PAPAIOS) - Kagawa, Shigemi; Nishimura, Kazuhiko; Wiedmann, Thomas; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The Journal of Economic Structures is a peer-reviewed international journal that publishes theoretical and empirical articles that apply to a wide range of formal analytical instruments and statistical techniques to explore the structural interdependencies among various activities immanent in the economy. We collect manuscripts dealing with broad issues, covering subjects such as technological innovations and lifestyle changes, trade and commerce, networks, ecology and development, among others, where structural understanding is essential. The journal supports communication among various related disciplines and encourages contributions from regional practitioners. The journal also welcomes proposals for special issues reflecting the trends in structural economics and other related disciplines.
Keywords: Business; Management science; Statistics; Engineering; Economics; Economics, general; Business and Management, general; Engineering, general; Statistics, general